PENGARUH MOTIVASI TERHADAP MINAT MAHASISWA AKUNTANSI MENGIKUTI UJIAN CERTIFIED PUBLIC ACCOUNTANT (CPA) - Akhmad Zainul Abidin; Adi Darmawan Ervanto (Master of Accounting Universitas Trunojoyo Madura, 2015)
This research aims to empirically examine the influence of carrer motivation, economic motivation, degree of motivation and achievement motivation influence to respons accounting student to follow CPA Exam. This research used primary data by making inquiries in the form of questionnaires distributed to respondents who are are still active students in the accounting department of the Economics Faculty, Trunojoyo University.Population within this research was extention accountancy student of Economics Faculty Trunojoyo University about 84. So the population used as criteria based as a sample called research techniques or purposive sampling. The analytical method used is multiple regression analysis, in which multiple linear regression analysis aimed to determine the effect of the variables carrer motivation, economic motivation, degree of motivation and achievement motivation of effect respons accounting student to follow CPA Exam.The results of this research indicated that degree motivation does not significantly influence to respons accounting student to follow CPA Exam. While the carrer motivation, economic motivation, and achievement motivation significantly influence to respons accounting student to follow CPA Exam.